Numerical and Economic Analysis of Hydronic-Heated Anti-Icing Solutions on Underground Park Driveways - Kayaci, Nurullah; Kanbur, Baris Burak (MDPI, 2023)
Snow and ice forming on the entrance and exit driveways of underground car parks of buildings brings serious difficulties and risks in safe parking for vehicles in winter. Even though traditional methods such as chemical salt and snow plowing reduce slippery conditions on driveways, they also result in infrastructure- and environment-related damages. Hydronic heating is an alternative way to prevent snow and ice forming; thereby, the hydronic heating driveway (HHD) is a promising technique for energy-efficient and environment-friendly solutions. This study presents a time-dependent three-dimensional numerical heat transfer model for HHD applications with realistic boundary conditions and meteorological data in the MATLAB environment. After developing the numerical heat transfer model, the model is applied to a case study in Istanbul, Turkey and followed by an economic comparison with the commercial electrically-heated driveways (EHD) method that is applied in two different ways; applying the electric cables in (i) whole driveway and (ii) only tire tracks. Different escalation rates in natural gas and electricity, hot fluid inlet temperature, air temperature, and the number of parallel pipes are the main parameters in the case study. Results show that the decrease in pipe spacing drops the investment cost term but it needs a higher supplied fluid temperature for anti-icing, and therefore the operating cost term increases. Among other cases was the number of parallel pipes, with 50 being the most economically feasible solution for all air temperatures ranging from 0 degrees C to -10 degrees C. The economic comparison shows that the EHD with only tire tracks has the minimum total cost as it significantly decreased both the operating and investment cost terms. In case of an anti-icing requirement on the whole road surface, the HHD system was found to be preferable to the EHD whole driveway scenario at air temperatures of 0 degrees C and -5 degrees C, while it is more beneficial only for the high electricity escalation rates at the ambient temperature of -10 degrees C.
Keywords: numerical heat transfer; ground heat exchanger; anti-icing; hydronic heating; electric heating; economic analysis; green building; underground parking; SNOW-MELTING PAVEMENT; HEATING-SYSTEM; SOLAR-ENERGY; EXCHANGER; MODEL; PERFORMANCE; SIMULATION; BRIDGE; OPTIMIZATION; TECHNOLOGIES; Science & Technology - Other Topics; Environmental Sciences & Ecology